Retro walking treadmill training reduces C—reactive protein levels in overweight and obese young adults: A randomized comparative study - Ajith Soman; Sunil Chandy; Khalid Alkhathami; Baranitharan Ramamoorthy; Bijad Alqahtani (Health Science Reports, 2023)
Abstract Background and Aims Retro walking has been shown to acquire a greater metabolic cost, placing a higher cardiopulmonary demand on the body, when compared with forward walking at a similar speed. The aim of this study was to compare the effect of retro walking with that of forward walking on C‐reactive protein (CRP) levels, body mass index (BMI) and blood pressure (BP) and to understand the influence of independent factors namely systolic blood pressure (SBP), diastolic blood pressure (DBP) and BMI on CRP in untrained overweight and obese young adults. Methods This was a randomised controlled trial whereby 106 participants underwent either retro walking (n = 53) or forward walking (n = 53) treadmill training four times a week for 12 weeks before and after which CRP, BMI, and BP levels were measured. Comparison of the measured values before and after intervention and between the groups was done and influence of BMI and BP on CRP levels was determined. Results Both groups recorded a significant decrease (p < 0.001) in CRP, BMI, and BP levels postintervention. The participants who underwent retro walking training showed a significantly (p < 0.001) higher decrease in all the outcomes as compared with the forward walking group. C‐reactive protein levels were seen to be influenced by BMI and DBP. Conclusion Retro‐walking training leads to greater decrease in CRP, BMI, and BP when compared with forward walking, and CRP levels are influenced by BMI and DBP. Retro walking treadmill training can be used preferentially to bring about reduction in cardiovascular risk factors.